AN ANALYSIS OF FIGURATIVE LANGUAGE ON THE SONG LYRICS “YOU ARE MY SUNSHINE” BY ANNE MURRAY - Vinanda Yusnitasari; Wulan Wangi; Yuli Sugianto (LUNAR, 2022)
Figurative language is language used to express something beyond the literal meaning. There are thirteen types of figurative language used in this research, namely simile, methapor, personification, hyperbole, euphemism, symbolism, repetition, irony, sarcasm, paradox, antithesis, idioms and imagery. This research focuses in analysing the types of figurative language found on the song lyrics “You are My Sunshine”. The objective of the research is to know what the types of figurative language used on the Song Lyrics “You are My Sunshine” by Anne Murray and how the types of figurative language used on the Song Lyrics “You are My Sunshine” by Anne Murray. In this research, researchers used a descriptive qualitative method in analyzing data in the song lyrics. In collecting data, the research identified and classified the types of figurative language in the song lyrics. In analysis data, the research reads song lyrics, determines types of figurative language in song lyrics, sorting song lyrics to put into types of figurative language, conclusion. The results of the research found nine types of figurative language with a total of each types of figurative language, namely, methapor (3), hyperbloe (1), symbolism (1), repetition (1), idiom (2), imagery (1). From thirteen types of figurative language used in the song lyrics, nine types of figurative language are used in the song lyrics and four types of figurative language are not used in the song lyrics. Types of figurative language that is not in the song lyrics, because the sentence song lyrics is ordinary language sentence.